2020
DOI: 10.1249/mss.0000000000002443
|View full text |Cite
|
Sign up to set email alerts
|

Energy Requirements of Male Academy Soccer Players from the English Premier League

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 28 publications
6
53
2
Order By: Relevance
“…In accordance with training and match duration, "mean" weekly TD in the younger age-groups (U12-U14: ~20-22km•week −1 , range: 16-26 km) was similar between squads but less than that of the older age-groups (U15-U18: ~26 km•week −1 , range: 22-30 km). Interestingly, such data are largely comparable with our previous findings (over a 14-day period) (Hannon et al, 2021) and with mean weekly distances completed by adult EPL players (~26 km•week −1 ), as also completed during a one game per week micro-cycle (Anderson et al, 2016). The increase in TD (and duration) in the older age-groups (U15-U18) also coincides with increases in chronological and biological age as most players have progressed through peak height velocity (PHV; Table 1).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In accordance with training and match duration, "mean" weekly TD in the younger age-groups (U12-U14: ~20-22km•week −1 , range: 16-26 km) was similar between squads but less than that of the older age-groups (U15-U18: ~26 km•week −1 , range: 22-30 km). Interestingly, such data are largely comparable with our previous findings (over a 14-day period) (Hannon et al, 2021) and with mean weekly distances completed by adult EPL players (~26 km•week −1 ), as also completed during a one game per week micro-cycle (Anderson et al, 2016). The increase in TD (and duration) in the older age-groups (U15-U18) also coincides with increases in chronological and biological age as most players have progressed through peak height velocity (PHV; Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, we recently quantified the training and match volume in male players from an English Premier League (EPL) academy over a two-week inseason period. We specifically observed that physical loading patterns (e.g., accumulative total distance) progressively increased from under (U)12/13 (38.3 ± 5.1 km), U15 (53.7 ± 4.5 km) and U18 (54.4 ± 7.1 km) age-groups (Hannon et al, 2021). Such increases in absolute training load in conjunction with increases in fat-free mass also resulted in increased total daily energy expenditure (TDEE) between age-groups (2859 ± 265, 3029 ± 262 and 3586 ± 487 kcal⋅day −1 in the U12/13, U15 and U18 agegroups, respectively) (Hannon et al, 2021).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…283 In addition, a subsequent study demonstrated that daily total energy expenditure (TEE) progressively increases as players transition through the academy pathway, likely a reflection of growth and maturation of key physical parameters as well as increased physical loading: U18 players presented with a TEE (3586±487 kcal/day) that was approximately 600 and 700 kcal/day higher than both the U15 (3029±262 kcal/day) and U12/13 players (2859±265 kcal/day), respectively. 284 Such differences in TEE is likely due to a combination of differences in anthropometric profile, RMR and physical loading between squads. An important finding is that TEE is comparable to or exceeds that previously reported in adult Premier League soccer players.…”
Section: Energy Demandsmentioning
confidence: 99%